2013
DOI: 10.1177/0885328213495426
|View full text |Cite
|
Sign up to set email alerts
|

A review of sternal closure techniques

Abstract: Sternotomy and sternal closure occur prior to and post cardiac surgery, respectively. Although post-operative complications associated with poor sternal fixation can result in morbidity, mortality, and considerable resource utilization, sternotomy is preferred over other methods such as lateral thoracotomy. Rigid sternal fixation is associated with stability and reduced incidence of post-operative complications. This is a comprehensive review of the literature evaluating in vivo, in vitro, and clinical respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 73 publications
0
55
0
6
Order By: Relevance
“…However, post-operative complications such as instability, deep sternal wound infection (DSWI) and non-union are associated with poor sternal fixation resulting in mortality, morbidity and resource utilization [4,5,6,7,8,9,10,11,12,13]. Alhalawani and Towler [14] conducted a systematic review of sternal closure techniques including wiring, interlocking, plating and cementation; discussing the relative advantages and disadvantages of each. It was concluded that all of these techniques have complications restricting their widespread adoption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, post-operative complications such as instability, deep sternal wound infection (DSWI) and non-union are associated with poor sternal fixation resulting in mortality, morbidity and resource utilization [4,5,6,7,8,9,10,11,12,13]. Alhalawani and Towler [14] conducted a systematic review of sternal closure techniques including wiring, interlocking, plating and cementation; discussing the relative advantages and disadvantages of each. It was concluded that all of these techniques have complications restricting their widespread adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Existing fixation devices for sternotomy fixation and repair have not gained widespread adoption [14]. Techniques including bands, staples, or wires are cost-effective however these fixation methods are unable to provide sufficient stabilisation, especially for patients with additional risks such as osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…It can take up to 3 months for the sternum to heal completely (44) Minimally invasive approaches are increasingly used in all surgical specialties. They are often popular with patients, promoted by industry, and are being adopted by surgeons (73)(74)(75).…”
Section: Choice Of Comparatorsmentioning
confidence: 99%
“…Simple wiring and figure of eight are performed by using four to eight stainless steel wires that can be passed directly through the sternum (transsternal technique) or through the intercostal spaces (peristernal or pericostal technique). 5,6 Multi-twist and Prakash techniques are performed through using multiple stainless-steel wires which are passed pericostally except in the manubrium where they are passed transsternally. 6,7 In Prakash technique; At least 6 wires have to be passed.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Multi-twist and Prakash techniques are performed through using multiple stainless-steel wires which are passed pericostally except in the manubrium where they are passed transsternally. 6,7 In Prakash technique; At least 6 wires have to be passed. The wires should run around the sternum in the intercostal spaces except in the manubrium where they have be passed through the bone.…”
Section: Introductionmentioning
confidence: 99%